How to Handle Concomitant Asymptomatic Prosthetic Joints During an Episode of Hematogenous Periprosthetic Joint Infection, a Multicenter Analysis. (18th August 2020) - Wouthuyzen-Bakker, Marjan; Sebillotte, Marine; Arvieux, Cédric; Fernandez-Sampedro, Marta; Senneville, Eric; Barbero, José Maria; Lora-Tamayo, Jaime; Aboltins, Craig; Trebse, Rihard; Salles, Mauro José; Kramer, Tobias Siegfried; Ferrari, Matteo; et al.
Abstract: Background: Prosthetic joints are at risk of becoming infected during an episode of bacteremia, especially during Staphylocococcus aureus bacteremia. However, it is unclear how often asymptomatic periprosthetic joint infection (PJI) occurs, and whether additional diagnostics should be considered. Methods: In this multicenter study, we retrospectively analyzed a cohort of patients with a late acute (hematogenous) PJI between 2005–2015 who had concomitant prosthetic joints in situ. Patients without at least 1 year of follow-up were excluded. Results: We included 91 patients with a hematogenous PJI and 108 concomitant prosthetic joints. The incident PJI was most frequently caused by Staphylococcus aureus (43%), followed by streptococci (26%) and Gram-negative rods (18%). Of 108 concomitant prosthetic joints, 13 were symptomatic, of which 10 were subsequently diagnosed as a second PJI. Of the 95 asymptomatic prosthetic joints, 1 PJI developed during the follow-up period and was classified as a "missed" PJI at the time of bacteremia with S. aureus (1.1%). Infected prosthetic joints were younger than the noninfected ones in 67% of cases, and prosthetic knees were affected more often than prosthetic hips (78%). Conclusions: During an episode of hematogenous PJI, concomitant asymptomatic prosthetic joints have a very low risk of being infected, and additional diagnostic work-up for these joints is not necessary. Abstract : We evaluated a cohort of patients with hematogenous periprosthetic joint infection and concomitant asymptomatic prosthetic joints. We demonstrate that if a prosthetic joint is asymptomatic, the chance of infection is very low. These joints do not require additional diagnostic work-up.